A mathematical model of selecting transport facilities for multimodal freight transportation - Lingaitienė, Olga (Transport, 2008)
A system of functional relationships between speed, traffic safety and costs, based on a set of criteria describing transportation quality is presented. The overall technological costs of transportation can be determined, when the costs of using road, rail and sea transport are calculated. For this purpose, a case study of creating a mathematical model for choosing the optimal route, taking into account time, costs and safety of transportation, is considered. The model evaluates the time of freight loading and storage at terminals. The total time of transportation, loading and storage differs for particular routes, depending on route structure and terminal operation. Freight safety is calculated in terms of insurance payments, depending on the type of goods, route and time of transportation. The model may be used for calculating any route, when applying the data on particular parks of vehicles.First published online: 27 Oct 2010